Організація навчального процесу з офтальмології в контексті болонської декларації - Завгородня, Наталія Григорівна; Саржевська, Людмила Едуардівна; Неділька, Володимир Іванович; Zavgoriodnjaja, N. G.; Sarzhevskaja, L. E.; Nedelka, W. I. (My University, 2009)
Положення Болонської декларації підлягає постійному впровадженню в навчальний процес вищих медичних навчальних закладів. У роботі розглядаються питання викладання офтальмології за кредитно-модульною системою. Перехід до кредитно-модульної системи викладання сприяє підвищенню мотивації студентів до освіти протягом усього періоду навчання. The main aspects of Bolognian declaration should be introducted in the training process of the higher medical educational institutions. Questions of the teaching of ophthalomology concerning the credit- modular system are examined in the work. Branching to the credit- modular system of teaching contributes to an increase in the motivation of students to the education during the period of studing.
The organization of training process in ophthalomology in the context of bolognian declaration
Keywords: офтальмологія; кредитно-модульна система; професійна мотивація; ophthalomology; credit- modular system; professional motivation